LANGUAGE MAINTENANCE AND SOLIDARITY AMONG AFRICAN AMERICANS - Sastika Seli (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This article aims to explain the language phenomena in sociolinguistics. namely, Ianguage maintenance and solidarity. Language maintenance is the phenomena u'here the speakers of the language maintain to use the language without affected by other languages nearby. This language maintenance may be influenced by solidarity inside the language community. The analysis derived from my previous research of "English spoken in Oakland and Atlanta in movie Romeo Must Die and Beauty Shop". The phenomena were drawn from the context of the movies where the speakers used African-American Vernacular English (AAVE) in their daily communication. African American is a minority language community in America compared to native speakers of American English. With a good solidarity among the black, they were not realy influenced by English used by the white American although there is still a language contact among them. They tend to make a gap betrveen their communitr and the outsider. Besides. their culture also influences the language maintenance among them. Rap and Hiphop culture is everyr.vhere in this rvorld. It is also one of the reasons why AAVE is not only used by African American as the minority but also used by' many peopie as the fan of these music genres. It creates more solidarity inside the community. This is also the reason African-American still use their AAVE in everyday communication in everv situation with other different language speakers, too.